1998
DOI: 10.1094/cchem.1998.75.1.156
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Kernel Characteristics of Hard Winter Wheats in Relation to Milling and Baking Quality

Abstract: Cereal Chem. 75(1):156-161To investigate relationships of wheat single kernel (SK) characteristics with end-use properties, we used 12 hard winter wheat cultivars harvested at six regions in Kansas in 1993. Significant positive correlations occurred among wheat hardness parameters including near-infrared reflectance hardness score, SK hardness index (SK-HI), and SK peak force (SK-PF) obtained by the Single Kernel Characterization System (SKCS). The SKCS characteristics also were significantly correlated to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
60
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 9 publications
7
60
3
Order By: Relevance
“…MANEV et al (1996) evidenced a negative relation between GI of Czech wheat and flour wet gluten content. These results agreed with the investigations of HOMMO et al (1991), who found a negative correlation of wheat GI (TIPPLES et al 1974;PØÍHODA 1980;RUBENTHALER et al 1987;OHM et al 1998). The evidence of relations depends on the testing methods used, above all on baking test.…”
supporting
confidence: 90%
“…MANEV et al (1996) evidenced a negative relation between GI of Czech wheat and flour wet gluten content. These results agreed with the investigations of HOMMO et al (1991), who found a negative correlation of wheat GI (TIPPLES et al 1974;PØÍHODA 1980;RUBENTHALER et al 1987;OHM et al 1998). The evidence of relations depends on the testing methods used, above all on baking test.…”
supporting
confidence: 90%
“…Hardness index was significantly correlated with flour yield and the proportion of break flour in Korean wheats with all puroindoline genotypes, but no significant relationships were found in Korean hard wheats. However, hardness index was negatively correlated with flour yield in hard wheats (Ohm et al 1998, Martin et al 2001 and Chinese winter wheats (Zhang et al 2005) and also negatively correlated with break flour yield in US wheats with various puroindoline genotypes (Bettge and Morris 2000).…”
Section: Discussionmentioning
confidence: 95%
“…Inverse relationships between the grain protein content and yield have been reported Ronalds 1984, Fischer et al 1989). In terms of kernel quality, inverse relationships have been reported between the kernel size and protein content (O'Brien and Ronalds 1984), and between the kernel size and loaf volume (Ohm et al 1998). In the current study, the mean protein content was lower in the F 4 than in the F 3 population, while the opposite held true for the mean kernel weight and diameter (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Harder wheat grains can produce flour with a larger particle size index, and a higher content of damaged starch, characteristics which contribute to a higher breadquality (Osborne et al 1997, Ohm et al 1998. Grain hardness is mainly controlled by puroindoline a and b, proteins encoded by the Pina and Pinb genes, that are tightly linked to the Ha locus on chromosome 5D (Giroux and Morris 1998).…”
Section: Introductionmentioning
confidence: 99%